2006
DOI: 10.1038/sj.pcan.4500906
|View full text |Cite
|
Sign up to set email alerts
|

Performance of tPSA and f/tPSA for prostate cancer in Chinese. A systematic review and meta-analysis

Abstract: Performing a systematic review and meta-analysis to evaluate the diagnostic performance of the total prostate-specific antigen (tPSA) tests for diagnosis of prostate cancer among Chinese. Literatures related to diagnosis of prostate cancer by tPSA and the ratio of free to total PSA (f/tPSA) being retrieved in five electronic databases. Sensitivity, specificity, positive likelihood ratio, negative likelihood ratio and diagnostic odds ratio (DOR) were pooled using random effects models. Summary receiver operatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
1
9
1
Order By: Relevance
“…The most common PSA derivative is the ratio of free PSA to total PSA, and the recommend cut-off is 0.14–0.16 in some Asian countries. 83 84 However, the effects of PSA derivatives are affected by differences in prostate volume. Lam et al .…”
Section: Diagnosismentioning
confidence: 99%
“…The most common PSA derivative is the ratio of free PSA to total PSA, and the recommend cut-off is 0.14–0.16 in some Asian countries. 83 84 However, the effects of PSA derivatives are affected by differences in prostate volume. Lam et al .…”
Section: Diagnosismentioning
confidence: 99%
“…The most accurate PSA derivative is the ratio of free PSA to total PSA, and the recommend cutoff is 0.14-0.16 in some Asian countries. 68,69 At the same time, PSA density, PSA velocity and PSA doubling time are also used occasionally. 70 A combination of these indices may reduce the number of repeat biopsies when the PSA level is between 4 and 10 ng ml 21 .…”
Section: Prostate Cancer (Pca) Epidemiological Characteristicsmentioning
confidence: 99%
“…Although several studies of %fPSA in China indicated an improvement in diagnostic accuracy over PSA alone [12] , [13] , these studies were mostly published in Chinese journals with limitations with respect to sample size. In this study, we attempted to examine the effectiveness of %fPSA in a retrospective multi-center Chinese cohort.…”
Section: Introductionmentioning
confidence: 99%